Splenic Vein Leiomyosarcoma: Case Report and Review of the Literature - Patrono, Damiano; Molinaro, Luca; Mazza, Elena; Romagnoli, Renato; Salizzoni, Mauro (JOP. Journal of the Pancreas, 2014)
Context Primary venous leiomyosarcoma (LMS) is a rare disease, most commonly affecting the retroperitoneal veins and in particular the inferior vena cava. Five-year survival rate ranges between 33% and 68%. Case Report Complete surgical resection represents the only potentially curative treatment, occasionally achieving long-term survival. LMS of the splenic vein is extremely rare, with only three cases reported in the literature. Conclusion We report a case of primary venous LMS arising from the splenic vein and we briefly review the relevant literature. Image: Intraoperative snapshot.